A Case for Thalamic Mechanisms of Schizophrenia: Perspective From Modeling 22q11.2 Deletion Syndrome - Jiang, Yanbo; Patton, Mary H.; Zakharenko, Stanislav S. (Frontiers in Neural Circuits, 2021)
Schizophrenia is a severe, chronic psychiatric disorder that devastates the lives of millions of people worldwide. The disease is characterized by a constellation of symptoms, ranging from cognitive deficits, to social withdrawal, to hallucinations. Despite decades of research, our understanding of the neurobiology of the disease, specifically the neural circuits underlying schizophrenia symptoms, is still in the early stages. Consequently, the development of therapies continues to be stagnant, and overall prognosis is poor. The main obstacle to improving the treatment of schizophrenia is its multicausal, polygenic etiology, which is difficult to model. Clinical observations and the emergence of preclinical models of rare but well-defined genomic lesions that confer substantial risk of schizophrenia (e.g., 22q11.2 microdeletion) have highlighted the role of the thalamus in the disease. Here we review the literature on the molecular, cellular, and circuitry findings in schizophrenia and discuss the leading theories in the field, which point to abnormalities within the thalamus as potential pathogenic mechanisms of schizophrenia. We posit that synaptic dysfunction and oscillatory abnormalities in neural circuits involving projections from and within the thalamus, with a focus on the thalamocortical circuits, may underlie the psychotic (and possibly other) symptoms of schizophrenia.